Komunikasi Publik terhadap Upaya Meningkatkan Kesadaran Masyarakat dalam Membayar Pajak Restoran - Cleopatra Amanda Putri; Kadek Dristiana Dwivayani (Syntax Corporation, 2023)
This study looks at the picture of public communication used by Bapenda in raising public awareness to pay restaurant tax. This study aims to determine the types of public communication used by Bapenda in conducting socialization to increase public awareness to pay restaurant tax and to find out the supporting and inhibiting factors of public awareness to pay restaurant tax in Samarinda City. This type of research is a type of qualitative research with phenomenological methods. The data collection methods used were interviews, observations and literacy studies and documentation. In determining the research subject, researchers use the Purposive Sampling Technique. The data analysis techniques used are collecting data, reducing data, presenting data and drawing conclusions. The results showed that Bapenda continues to improve and innovate by conducting public communication to the public and creating websites and social media to disseminate information related to restaurant taxpayers to the restaurant owner community. This is also reinforced by information as one of the tax-abiding communities that the strategy used by Bapenda is effective enough to be carried out to increase public awareness to pay restorsn tax. The supporting factors of public communication carried out by Bapenda consist of restaurant owners who are in the place of socialization, education after registration, the existence of the SIMPAD Web, online tax payments and optimization of social media. Meanwhile, the inhibiting factors of public communication are the lack of public education related to Web SIMPAD, lack of activity on social media and the absence of shop owners during socialization.